The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00213-006-0467-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging research in human MDMA users: a review

Abstract: Rationale Determining whether, under what circumstances, and to what extent 3,4-methylenedioxymethamphetamine (MDMA) exposure produces chronic changes in human brain function is a critical public health issue. MDMA is a widely used recreational drug commonly sold as "Ecstasy". Because findings from the animal literature have indicated that specific dosage regimens of MDMA can produce longlasting alterations in serotonergic function, existing studies of MDMA effects in humans have examined brain serotonin (5-HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 105 publications
(171 reference statements)
1
61
0
6
Order By: Relevance
“…We further argue that such a conclusion has potential clinical relevance for the treatment of Ecstasy users who are suffering from cognitive, mood, or anxiety disorders that may be related to their substance use. Although the overall single-day dose of 40 mg/kg of MDMA used in the present study is clearly much greater than recreational human doses, SERT imaging studies of users raise the possibility that cumulative exposure involving many smaller Ecstasy doses could, over time, produce the kind of serotonergic neurotoxicity seen in animal binge studies (Cowan, 2007). Finally, some websites aimed at the general public suggest that taking an SSRI with Ecstasy can prevent the adverse side effects of MDMA, which may be a fallacious assumption based in part on the present results.…”
Section: Discussionmentioning
confidence: 83%
“…We further argue that such a conclusion has potential clinical relevance for the treatment of Ecstasy users who are suffering from cognitive, mood, or anxiety disorders that may be related to their substance use. Although the overall single-day dose of 40 mg/kg of MDMA used in the present study is clearly much greater than recreational human doses, SERT imaging studies of users raise the possibility that cumulative exposure involving many smaller Ecstasy doses could, over time, produce the kind of serotonergic neurotoxicity seen in animal binge studies (Cowan, 2007). Finally, some websites aimed at the general public suggest that taking an SSRI with Ecstasy can prevent the adverse side effects of MDMA, which may be a fallacious assumption based in part on the present results.…”
Section: Discussionmentioning
confidence: 83%
“…As reviewed previously (Cowan, 2007;Cowan et al, 2008a), previous studies employing more complex cognitive paradigms found a range of activation patterns following chronic MDMA exposure (Daumann et al, 2003(Daumann et al, , 2004(Daumann et al, , 2005Jager et al, 2008a, b;Jacobsen et al, 2004;Moeller et al, 2004). Subsequent studies have revealed a similarly mixed picture when using fMRI to examine brain activation during cognitive paradigms (Roberts et al, 2009).…”
Section: Relationship To Previous Findingsmentioning
confidence: 93%
“…However, matching average use across groups does not account fully for individual patterns in drug exposure and also controls only for the most commonly used substances (e.g., cannabis). Third, most studies investigating MDMA effects on human neurophysiology have employed paradigms that involve the performance of complex cognitive tasks during functional neuroimaging (reviewed by Cowan, 2007). However, interpreting functional neuroimaging findings arising from complex cognitive tasks in terms of underlying brain neurophysiology is challenging.…”
Section: Relationship To Previous Findingsmentioning
confidence: 99%
See 2 more Smart Citations